Co-creating digital services with and for facilities management. Issue 9 (4th July 2017) - Lavikka, Rita Henriikka; Lehtinen, Teemu; Hall, Daniel
Abstract : Purpose: This study aims to increase understanding about the co-creation of digital facilities management (FM) services with and for FM during a construction project. Design/methodology/approach: The paper reports a case study on the co-creation of a digital facilities management service during the Mission Bay medical center construction project for the University of California, San Francisco. The sub-contractors and the FM team co-created a quick-response (QR) code system for valves on the project. This digital service is now used by the FM team for training purposes and in emergency situations when information on valves and their service areas is quickly needed. Researchers made on-site observations, conducted 84 interviews and reviewed archival data in 2012, 2014 and 2016. Findings: The findings show that a successful co-creation process consists of three elements: a dialogue between the project parties, the creation of shared context between the project parties and the creation of shared understanding about the FM's needs and the service providers' ways of satisfying those needs. The study describes ways to promote these elements. Originality/value: Previous studies emphasize the need for digital FM but few explain how FM teams can be involved in creating digital services for them. This paper describes how to co-create digital FM services with and for FM in the context of a construction project.